Pembagian Warisan Bagi Anak Perempuan Ditinjau dari Hukum Adat Byak - Hamza Toatubun (Kyadiren, 2020)
This study aims to analyze the process of the inheritance distribution for girls and the factors that affects the development of girls' inheritance rights in terms of Byak Traditional law. This research is empirical juridical research. It was conducted in Inggiri Village, Biak-Papua. The analysis was carried out in a qualitative descriptive technique. The results showed that 1) The process of the inheritance distribution for occurs when the heir has died, where the position of the heir is taken over automatically to the heirs who are part of the clan (keret) or biological children. The girls can be given inheritance (Kayan) on condition that a traditional ceremony (Wor) is carried out as a traditional recognition but gets a smaller share than boys as the successors of the family's descendants (Keret). 2) The factors that influence the development of the inheritance rights are economic factors, educational factors, and social factors. The most prominent is educational factors because civilization and the society gradually develop following a more advanced education standard and religion as a facilitating intercommunication.